Fermented and distilled alcoholic beverages: A technological, chemical and sensory overview: Red wines - De Castilhos, M. Bonatto Machado; Del Bianchi, Vanildo Luiz [UNESP]; Manfroi, Vitor (My University, 2021)
Red Wines presents relevant material regarding red wine technologies and their variations, including current information about their chemistry and sensory profiles. The book provides crucial evidence regarding the use of novel technologies in red wines and discusses the relationship between chemical and sensory approaches, since both are closely related. This information will be useful for red wine producers, scientists and professors, and will be helpful as material for food science, technology and engineering graduate and post-graduate students. This book includes seven chapters with the following subject matter: red wines produced from American grapes (Vitis labrusca) (Brazil), Bordeaux Cabernet Sauvignon and Merlot (France), Tempranillo (Spain), Carmenère (Chile), Touriga Nacional (Portugal), Tannat (Uruguay), and Syrah (Brazil) grapes. The distinctiveness of this book lies in the fact that it provides information concerning the use of novel technologies in red wine production, comparing those with classical technologies used worldwide. The book provides useful data regarding the effect of these novel technologies on chemical properties, sensory wine acceptance and descriptive profiles, assessing the changes promoted in the wines’ chemical profile as a result of the their quality improvement and sensory uniqueness.